Design and development of robotic manta ray - Marvin Sugi Hartono. (2009)
Numerous research projects have been conducted to invent an efficient, maneuverable, and yet eco-friendly underwater propulsion system. Being inspired by nature, this biomimetic related mechatronics project aimed to develop a robotic manta ray featuring flexible pectoral fin flapping mechanism for its underwater propulsion. This project emphasized heavily on the design and construction of the flapping mechanism.